Anatomy and physiology for midwives - Coad, Jane; Dunstall, Melvyn (Churchill Livingstone/Elsevier, 2011)
Suitable for all students of midwifery, this title provides a review of anatomy and physiology applicable to midwifery, from first principles through to advanced research, utilizing case studies for reflection